A participação escolar de alunos com deficiência na percepção de seus - Abe, Patricia Bettiol [UNESP]; Araújo, Rita de Cássia Tibério [UNESP] (FapUNIFESP (SciELO), 2010)
The identification of the level of school participation of disabled students is crucial for monitoring the inclusive educational process. It requires the use of measuring instruments that provide functionality before school specific demands, and that at the same time can motivate the teacher to reflect on his judgment about the performance of students with disabilities. School Function Assessment (SFA) is a tool that helps recognize the special needs of students with disabilities according to parameters of functionality and participation. Thus, this study analyzed the influence of the use of SFA on the teacher's judgment of student participation and performance. Eight teachers responded regarding the participation of nine students with disabilities through the use of the SFA and a questionnaire. The results indicated that, for five teachers, SFA helped with the perception of the student's participation, focusing on the activity demand and brought reflections on: the need of evaluation not just in the classroom, co-relation between the degree of disability and the participation of the student, understanding of the specificities of the performance, importance of the adaptation to neutralize incapacity and the importance of the focus deviation from the disability toward functionality.
School participation of students with disabilities from the perception of their teachers
Keywords: Occupational therapy; School inclusion; Special education; Student participation